Incidence of life-threatening events in children with Wolff-Parkinson-White syndrome: Analysis of a large claims database - Janson, Christopher M.; Millenson, Marisa E.; Okunowo, Oluwatimilehin; Dai, Dingwei; Christmyer, Zane; Tan, Reina Bianca; Ramesh Iyer, V.; Shah, Maully J.; O’Byrne, Michael L. (Heart rhythm, 2022)
Previous estimates of life-threatening event (LTE) risk in Wolff-Parkinson-White (WPW) syndrome are limited by selection bias inherent to tertiary care referral-based cohorts. This analysis sought to measure LTE incidence in children with WPW syndrome in a large contemporary representative population. A retrospective cohort study was conducted using claims data from the IBM MarketScan Research Databases, evaluating subjects with WPW syndrome (age 1–18 years) from any encounter between January 1, 2013, and December 31, 2018. Subjects with congenital heart disease and cardiomyopathy were excluded. The primary outcome was diagnosis of ventricular fibrillation (VF); a composite outcome, LTE, was defined as occurrence of VF and/or cardiac arrest. VF and LTE rates were compared to matched representative controls without WPW syndrome (3:1 ratio). The prevalence of WPW syndrome was 0.03% (8733/26,684,581) over a median follow-up of 1.6 years (interquartile range 0.7–2.9 years). Excluding congenital heart disease/cardiomyopathy, 6946 subjects were analyzed. An LTE occurred in 49 subjects (0.7%), including VF in 20 (0.3%). The incidence of VF was 0.8 events per 1000 person-years, and the incidence of LTE was 1.9 events per 1000 person-years. There were no occurrences of VF in controls; the rate of LTE was 70 times higher in subjects with WPW syndrome (0.7%; 95% confidence interval 0.5%–0.9%) than in controls (0.01%; 95% confidence interval 0%–0.02%). The use of a large claims data set allowed for an evaluation of VF and LTE risk in an unselected pediatric population with WPW syndrome. The observed range of 0.8–1.9 events per 1000 person-years is consistent with prior reports from selected populations. A comparison of event rates to matched controls confirms and quantifies the significant elevation in VF and LTE risk in pediatric WPW syndrome.